Prevalence of antibiotic resistance genes its association with microbiota in raw milk of northwest Xinjiang - Zhao, Yan; Niu, Yifan; Zhao, Min; Huang, Wanting; Qin, Yanan (Frontiers in Microbiology, 2025)
The issue of antibiotic resistance caused by antibiotic resistance genes (ARGs) has become a significant concern in environmental research in recent years, while raw milk is an important link in the food chain and has become one of the carriers and reservoirs of ARGs, which has not been taken seriously. This research employed high-throughput quantitative PCR and Illumina sequencing techniques targeting the 16S rRNA gene. These methods were used to examine the bacterial community composition and genes associated with antibiotic resistance in raw milk samples collected from the northwestern area of Xinjiang. An aggregate of 31 distinct resistance alleles were identified, with their abundance reaching as high as 3.70 × 105 copies per gram in the analyzed raw milk samples. Microorganisms harboring ARGs that confer resistance to beta-lactams, tetracyclines, aminoglycosides, and chloramphenicol derivatives were prevalent in raw milk. Procrustes analysis revealed a certain degree of correlation between the microbial community and the antibiotic resistance gene (ARG) profiles. Furthermore, network analysis demonstrated that Actinobacteria and Firmicutes were the predominant phyla exhibiting co-occurrence relationships with specific ARGs. Combining the findings from Variance Partitioning Analysis (VPA), the distribution of ARGs was mainly driven by three factors: the combined effect of physicochemical properties and mobile genetic elements (MGEs) (33.5%), the interplay between physicochemical parameters and microbial communities (31.8%), and the independent contribution of physicochemical factors (20.7%). The study demonstrates that the overall abundance of ARGs correlates with physicochemical parameters, bacterial community composition, and the presence of MGEs. Furthermore, understanding these associations facilitates the evaluation of antibiotic resistance risks, thereby contributing to enhanced farm management practices and the assurance of food safety.